İlköğretim kurumlarında görev yapmakta olan yöneticilerin kaynaştırma eğitimine ilişkin tutumları ile problem çözme becerileri arasındaki ilişkinin incelenmesi - Çinko, Nurcan (My University, 2004)
İlköğretim Kurumlarında Görev Yapmakta Olan Yöneticilerin Özel Eğitimde Kaynaştırma Eğitimine İlişkin Tutumları İle Problem Çözme Becerileri Arasındaki İlişkinin İncelenmesi konulu bu araştırmada şu soruların cevapları aranmıştır: 1.İlköğretim kurumlarında görev yapmakta olan yöneticilerin engelli çocuklar ile normal çocukların kaynaştırılmalarına ilişkin tutumları; kaynaştırma eğitimine ilişkin tutumlarının kurumdaki görevleri, cinsiyet, yaş, medeni durum, eğitim düzeyi, branşı, özel eğtimle ilgili bir eğitim programına katılma, eğitim programının türü, kurumda eğitim alan engelli çocuk sayısı, kurumda eğitim almakta olan çocukların özür gruplarına göre dağılımı, engelli bir çocuğa sahip olma, görev süresi, kaynaştırma eğitimi ile ilgili tecrübeleri ve kaynaştırma eğitimi ile ilgili bir eğitim programına katılma durumuna göre farklılaşmakta mıdır? 2.İlköğretim kurumlarında görev yapmakta olan yöneticilerin problem çözme becerileri ne düzeydedir? 3.İlköğretim kurumlarında görev yapmakta olan yöneticilerin problem çözme becerilerinin kurumdaki görevleri, cinsiyet, yaş, medeni durum, eğitim düzeyi, branşı, özel eğtimle ilgili bir eğitim programına katılma, eğitim programının türü, kurumda eğitim alan engelli çocuk sayısı, kurumda eğitim almakta olan çocukların özür gruplarına göre dağılımı, engelli bir çocuğa sahip olma, görev süresi, kaynaştırma eğitimi ile ilgili tecrübeleri ve kaynaştırma eğitimi ile ilgili bir eğitim programına katılma durumuna göre farklılaşmakta mıdır? 4.İlköğretim kurumlarında görev yapmakta olan yöneticilerin engelli çocuklar ile normal çocukların kaynaştırılmasına ilişkin tutumları ile problem çözme becerileri arasında bir ilişki var mıdır? İlişkisel tarama yaklaşımına uygun olarak düzenlenen araştırmanın evrenini, İstanbul İli Anadolu Yakasında bulunan ve Kaynaştırma eğitimi uygulanan okullarda görev yapmakta olan yöneticilerin tümü oluşturmaktadır. Örneklem için, İstanbul İli Anadolu Yakasında Üsküdar, Ümraniye ve Kadiköy semtlerinde bulunan ve kaynaştırma eğitimi uygulanan ilköğretim kurumlarında görev yapan 30 bayan ve 80 bay olmak üzere toplam 110 yöneticiye ulaşılmıştır. Veri toplamak amacıyla üç araç kullanılmıştır: 1.Kişisel Bilgiler Formu 2.Tutum Ölçeği 3.Problem Çözme Envanteri Verilerin çözümlenmesinde aşağıdaki istatistiksel analizler yapılmıştır: 1.İlköğretim kurumlarında engelli çocuklar ile normal çocukların birlikte eğitim almalarına (kaynaştırma=entegrasyon) karşı, bu eğitim kurumlarında görev yapmakta olan yöneticilerin tutum düzeyleri ile problem çözme düzeylerini belirlemek için aritmetik ortalamalar hesaplanmıştır. 2.Araştırmada, İlköğretim kurumlarındaki engelli çocuklar ile normal çocukların birlikte eğitim almalarına (kaynaştırma=entegrasyon) karşı, bu eğitim kurumlarında görev yapmakta olan yöneticilerin Kaynaştırma Eğitimine İlişkin Tutum düzeyleri nin çeşitli Kişisel Özelliklere göre farklılaşma durumunu belirlemek için t-Testi ve Varyans Analizi hesapları yapılmıştır. 3.Araştırmada, İlköğretim kurumlarında görev yapmakta olan yöeticilerin Problem Çözme Becerilerinin çeşitli Kişisel Özelliklere göre farklılaşma durumunu belirlemek için t-Testi ve Varyans Analizi hesapları yapılmıştır. 4. İlköğretim kurumlarındaki engelli çocuklar ile normal çocukların birlikte eğitim almalarına (kaynaştırma=entegrasyon) karşı, bu eğitim kurumlarında görev yapmakta olan yöneticilerin tutumları ile problem çözme becerileri arasındaki ilişkinin incelenmesi amacıyla Pearson Çarpım Momentler Korelasyon Katsayısı hesaplanmıştır. Araştırmadan elde edilen bulgular şunlardır: İlköğretim kurumlarında görev yapmakta olan yöneticilerin engelli çocuklar ile normal çocukların kaynaştırılmalarına ilişkin tutum puanları eğitim düzeyine göre .05 anlamlılık düzeyinde istatistiksel açıdan farklılaşmaktadır. Aritmetik ortalamalara göre yüksek lisans programına katılan yöneticilerin tutum puanları bir lisans programından mezun olan yöneticilere göre daha yüksektir. İlköğretim kurumlarında görev yapmakta olan yöneticilerin engelli çocuklar ile normal çocukların kaynaştırılmalarına ilişkin tutum puanları branşa göre .01 anlamlılık düzeyinde istatistiksel açıdan farklılaşmaktadır. Aritmetik ortalamalara göre sınıf öğretmenliği branşından mezun olan yöneticilerin tutum puanları diğer anabilim dallarından mezun olan yöneticilere göre daha yüksektir. İlköğretim kurumlarında görev yapmakta olan yöneticilerin engelli çocuklar ile normal çocukların kaynaştırılmalarına ilişkin tutum puanları özel eğitimle ilgili bir eğitim programına devam etme durumuna göre .01 anlamlılık düzeyinde istatistiksel açıdan farklılaşmaktadır. Aritmetik ortalamalara göre özel eğitimle ilgili bir eğitim programına katılan yöneticilerin tutum puanları alanla ilgili herhangi bir eğitim programına katılmayan yöneticilere göre daha yüksektir. İlköğretim kurumlarında görev yapmakta olan yöneticilerin engelli çocuklar ile normal çocukların kaynaştırılmalarına ilişkin tutum puanları kaynaştırma eğitimiyle ilgili bir eğitim programına devam etme durumuna göre .01 anlamlılık düzeyinde istatistiksel açıdan farklılaşmaktadır. Aritmetik ortalamalara göre kaynaştırma eğitimiyle ilgili bir eğitim programına katılan yöneticilerin tutum puanları alanla ilgili herhangi bir eğitim programına katılmayan yöneticilere göre daha yüksektir. İlköğretim kurumlarında görev yapmakta olan yöneticilerin problem çözme becerileri cinsiyet durumuna göre .01 anlamlılık düzeyinde istatistiksel açıdan farklılaşmaktadır. Aritmetik ortalamalara göre bayan yöneticilerin problem çözme becerileri erkek yöneticilere göre daha yüksektir. İlköğretim kurumlarında görev yapmakta olan yöneticilerin problem çözme becerileri kaynaştırma ile ilgili bir eğitim programına katılma durumuna göre .01 anlamlılık düzeyinde istatistiksel açıdan farklılaşmaktadır. Aritmetik ortalamalara göre kaynaştırma ile ilgili herhangi bir eğitim programına katılmayan yöneticilerin problem çözme becerileri eğitim programına katılan yöneticilere göre daha yüksektir. İlköğretim kurumlarında görev yapmakta olan yöneticilerin kaynaştırma eğitimi ile ilgili tutumları ve problem çözme becerileri arasında .01 anlamlılık düzeyinde bir ilişki görülmektedir. İlişki negatif yönlüdür. Buna göre, kaynaştırma eğitimi ile ilgili tutum düzeyi arttıkça problem çözme beceri düzeyi azalmaktadır. İlköğretim kurumlarında görev yapmakta olan erkek yöneticilerin kaynaştırma eğitimi ile ilgili tutumları ve problem çözme becerileri arasında .01 anlamlılık düzeyinde bir ilişki görülmektedir. İlişki negatif yönlüdür. Buna göre, ilköğretim kurumlarında görev yapmakta olan erkek yöneticilerin kaynaştırma eğitimi ile ilgili tutum düzeyi arttıkça problem çözme beceri düzeyi azalmaktadır. İlköğretim kurumlarında görev yapmakta olan lisans mezunu yöneticilerin kaynaştırma eğitimi ile ilgili tutumları ve problem çözme becerileri arasında .01 anlamlılık düzeyinde bir ilişki görülmektedir. İlişki negatif yönlüdür. Buna göre, ilköğretim kurumlarında görev yapan lisans mezunu yöneticilerin kaynaştırma eğitimi ile ilgili tutum düzeyi arttıkça problem çözme beceri düzeyi azalmaktadır. İlköğretim kurumlarında görev yapmakta olan sınıf öğretmenliği mezunu yöneticilerin kaynaştırma eğitimi ile ilgili tutumları ve problem çözme becerileri arasında .01 anlamlılık düzeyinde bir ilişki görülmektedir. İlişki negatif yönlüdür. Buna göre, ilköğretim kurumlarında görev yapmakta olan sınıf öğretmenliği mezunu yöneticilerin kaynaştırma eğitimi ile ilgili tutum düzeyi arttıkça problem çözme beceri düzeyi azalmaktadır. Answers to the following questions were searched in this research with title of Analysis of Relations between the Problem Solving Skills and Attitudes in Regard of Education for Integration in Special Education of Managers Serving in The Primary Education Institutions: 1. Do attitudes of managers in charged in primary education institutions in regard of integration of disabled children with normal children differentiate according; to their duties in regard of their attitudes toward integration education, to their gender, to their age, to their marital status, to their level of education, to their field of occupation, to their participation to an education program related with special education, to kind of education program they participated, number of disabled children educated in the institution they are in, to distribution of disabled children educated in the institution they are in as per disability categories, to they have a disabled child, to their terms of duty (seniority), to their experience in integration education, to their participation to an education program related with integration education institutions? 2. What are levels of problem solving skills of managers serving in primary education? 3. Do problem solving skills of managers serving in primary education institutions differentiate according; to their duties in the institution, to their gender, to their age, to their marital status, to their level of education, to their field of occupation, to their participation to an education program related with special education, to kind of education program they participated, number of disabled children educated in the institution they are in, to distribution of disabled children educated in the institution they are in as per disability categories, to they have a disabled child, to their terms of duty (seniority), to their experience in integration education, to their participation to an education program related with integration education institutions? 4. Is there a relationship between the attitudes of managers serving in primary education institutions in regard of their integration of disabled children with normal ones and the problem solving skills of same in the same regard? Research universe formed in compliance with relational scanning approach is formed by all managers in duty in schools located in Anatolian side of province of Istanbul and the integration education is applied. Totally 100 managers, 30 female and 80 male, are accessed those are in duty in schools located in Üsküdar, Ümraniye and Kadıköt districts of Anatolian side of province of Istanbul and in duty in primary education institutions where the integration education is applied. Three tools were utilized for data gathering: 1. Personal information form 2. Attitude scale 3. Problem solving inventory Following statistical analysis were carried in analysis of data: 1. Arithmetical averages were calculated in order to determine the level of attitudes and problem solving skills of managers in charged of primary education institutions towards disabled children and normal children get an integrated education in these education institutions. 2. t-Test and Variance Analysis were carried in order to determine the differentiation of Level of Attitudes in regard of Integrated Education as per Personal Characteristics of managers in charged of primary education institutions towards disabled children and normal children get an integrated education in these education institutions. 3. t-Test and Variance Analysis were carried in order to determine the differentiation of Problem Solving Skills as per Personal Characteristics of the managers in charged of primary education institutions. 4. Pearson Product Moments Correlation Coefficient is calculated in order to analyze the relationship between attitudes and problem solving skills of the managers in charged in primary education institutions towards disabled children and normal children get an integrated education in these education institutions. Findings of the research are as follows: 1. Attitude scores of managers in charged in primary education institutions in regard of integrated education of disabled children with normal children statistically differentiate at the significance level of 0.5 as per their level of education. According to the arithmetical averages attitude scores of managers participated to a post-graduate education program (Master of Science degree) are higher than of those possess a graduate level education program (Bachelor of Science degree). 2. Attitude scores of managers in charged in primary education institutions in regard of integrated education of disabled children with normal children statistically differentiate at the significance level of 0.1 as per their field of occupation. According to the arithmetical averages attitude scores of managers graduated from class teacher branch are higher than of those graduated from other main science branches. 3. Attitude scores of managers in charged in primary education institutions in regard of integrated education of disabled children with normal children statistically differentiate at the significance level of 0.1 as per their participation to an education program related with special education. According to the arithmetical averages attitude scores of managers participated to an education program related with special education are higher than of those not participated to an education program related with special education. 4. Attitude scores of managers in charged in primary education institutions in regard of integrated education of disabled children with normal children statistically differentiate at the significance level of 0.1 as per their participation to an education program related with integrated education. According to the arithmetical averages attitude scores of managers participated to an education program related with integrated education are higher than of those not participated to an education program related with integrated education. 5. Problem solving skills of managers in charged in primary education institutions statistically differentiate at the significance level of 0.1 as per their gender. According to the arithmetical averages attitude scores of male managers are higher than of female managers. 6. Problem solving skills of managers in charged in primary education institutions statistically differentiate at the significance level of 0.1 as per their participation to an education program related with integrated education. According to the arithmetical averages, problem solving skills of managers not participated to an education program related with integration education are higher than of those participated to an education program related with integration education. 7. A relationship at a level of significance of 0.1 is observed between attitudes in regard of integrated education of the managers in charged in primary education institutions and their problem solving skills. This relationship is in negative direction. According to this relation, as much as attitude level in regard of integrated education increases, level of problem solving skills deceases. 8. A relationship at a level of significance of 0.1 is observed between attitudes in regard of integrated education of male managers in charged in primary education institutions and their problem solving skills. This relationship is in negative direction. According to this relation, as much as attitude level of male managers in charged in primary education institutions in regard of integrated education increases, their level of problem solving skills deceases. 9. A relationship at a level of significance of 0.1 is observed between attitudes in regard of integrated education of managers possess a graduate level education program (Bachelor of Science degree) in charged in primary education institutions and their problem solving skills. This relationship is in negative direction. According to this relation, as much as attitude level of managers possess a graduate level education program (Bachelor of Science degree) in charged in primary education institutions in regard of integrated education increases, their level of problem solving skills deceases. 10. A relationship at a level of significance of 0.1 is observed between attitudes in regard of integrated education of managers graduated from main science branch of class teacher in charged in primary education institutions and their problem solving skills. This relationship is in negative direction. According to this relation, as much as attitude level of managers graduated from main science branch of class teacher in charged in primary education institutions in regard of integrated education increases, their level of problem solving skills deceases.
Keywords: Eğitim; Okul idaresi ve yönetimi; Okul organizasyonu ve yönetimi